Pengaruh Efektifitas Manajemen Organisasi Cordofa Medan dalam Meningkatkan Motivasi Beribadah bagi Para Mualaf - Handayani, Dwi Indah (Fakultas Dakwah UIN KHAS Jember, 2024)
With the increasing number of converts to Islam in Indonesia, Cordofa, as a philanthropic organization, conducts specific outreach activities focused on training converts in religious practices. After deciding to embrace Islam, converts, who come from diverse backgrounds, often face various challenges. Many of them lose their homes and jobs, and are expelled from their families who reject their religious choice. This study uses a quantitative research method. The results of this study indicate that the t-value (tₕᵢₜᵤₙg) is 4.999 and the significance level (sig.) is 0.000. The critical value for t (tₜₐbₑₗ) with degrees of freedom (df) n-44 at α 0.05 is 1.680. Since the t-value (4.999) is greater than the critical value (1.680) and the significance level (0.000) is less than 0.05, H₀ is rejected and H₁ is accepted, meaning that the effectiveness of the organization has a significant influence on the motivation of converts in their religious practices. The findings show that the t-value is 4.999 and the significance level is 0.000. Therefore, we can conclude that the t-value (4.999) is greater than the critical value (1.680) and the significance level (0.000) is less than 0.05. Hence, H₀ is rejected and H₁ is accepted, indicating that the effectiveness of the organization has a significant impact on the motivation of converts in their religious practices.